Radiatively driven convection: diffusivity-free regimes of geophysical and astrophysical flows in the laboratory - Hadjerci, Gabriel; Bouillaut, Vincent; Miquel, Benjamin; Aumaître, Sébastien; Gallet, Basile (Comptes Rendus. Physique)
We consider the turbulent heat transport induced by thermal convection. The widespread belief is that the transport properties of the turbulent flow should be independent of the tiny molecular diffusivities for asymptotically strong driving, but the associated “ultimate” scaling regime proves challenging to observe experimentally using standard convection cells (Rayleigh–Bénard geometry). We thus recently introduced an alternate experimental setup where convection is driven radiatively, with internal heating within the lower region of the body of fluid. This setup naturally leads to the ultimate regime of thermal convection. We then discuss how adding global rotation to the experimental setup has led to the first laboratory observation of the diffusivity-free regime of rapidly rotating turbulent convection, also known as the “geostrophic turbulence” scaling regime.